Petroleum ether extract of Ophiorrhiza eriantha Wight induces apoptosis in human breast cancer MCF-7 cell line - Abdul Jaleel, Malarkodi Velraj (Journal of Applied Pharmaceutical Science, 2022)
Ophiorrhiza mungos is a traditionally used anticancer plant and is a source of monoterpene indole alkaloid camptothecin. Ophiorrhiza eriantha Wight is a poorly studied allied species of O. mungos. In the present study, we compared the in vitro anticancer activity of different extracts of O. eriantha Wight with O. mungos. Petroleum ether extract of aerial part of O. eriantha Wight (OEAPE) was found to be the most active among the 12 extracts. 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay on Michigan Cancer Foundation-7 (MCF-7) cell line was conducted and OEAPE shows significant activity. OEAPE induced apoptosis and an in-depth examination of the apoptotic process was carried out. After a statistical data analysis of results of Acridine orange assay, Western Blot analysis of p53, Bcl-2, Bax, caspase-7, caspase-9, Flow cytometry, and DNA fragmentation assay, it is evident that OEAPE induces apoptosis in breast cancer cell line (MCF-7).
Keywords: Apoptosis, DNA fragmentation assay, flow cytometry, MCF-7 cell line, MTT assay, Ophiorrhiza eriantha Wight